2021
DOI: 10.3390/nu13041143
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Breast Milk-Derived Lactobacillus rhamnosus Probio-M9 on Colitis-Associated Carcinogenesis by Restoration of the Gut Microbiota in a Mouse Model

Abstract: Chronic inflammation is a risk factor for colorectal cancer, and inflammatory cytokines secreted from inflammatory cells and active oxygen facilitate tumorigenesis. Intestinal bacteria are thought to regulate tumorigenesis. The longer the breastfeeding period, the lower is the risk of inflammatory bowel disease. Here, we investigated preventive effects of the probiotic Lactobacillus rhamnosus M9 (Probio-M9) on colitis-associated tumorigenesis. An inflammatory colorectal tumor model was established using a 6-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 32 publications
5
45
0
Order By: Relevance
“…This study evaluated the effect of the probiotic, L. rhamnosus Probio-M9, on anti-PD-1-based ICB treatment using a heterotopic in vivo model of colorectal cancer constructed in mice with antibiotic-disrupted gut microbiota. It is interesting to note that taking probiotics after administration of antibiotics enhanced the tumor growth inhibitory effect in subsequent ICB treatment; such tumor inhibitory effect was significantly stronger than that in non-probiotic-treated mice ( P < 0.05), which was consistent with the observations of a previous study ( 24 ), showing that Probio-M9 could promote the therapeutic efficacy in both orthotopic and ectopic colon cancer.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study evaluated the effect of the probiotic, L. rhamnosus Probio-M9, on anti-PD-1-based ICB treatment using a heterotopic in vivo model of colorectal cancer constructed in mice with antibiotic-disrupted gut microbiota. It is interesting to note that taking probiotics after administration of antibiotics enhanced the tumor growth inhibitory effect in subsequent ICB treatment; such tumor inhibitory effect was significantly stronger than that in non-probiotic-treated mice ( P < 0.05), which was consistent with the observations of a previous study ( 24 ), showing that Probio-M9 could promote the therapeutic efficacy in both orthotopic and ectopic colon cancer.…”
Section: Discussionsupporting
confidence: 90%
“…At day 24, the mean tumor volume of CT group (both anti-PD-1 antibody and probiotics; mean tumor size ± SEM = 1,681.02 ± 77.86 mm 3 ) was the smallest, followed by MC group (received anti-PD-1 antibody but not probiotics; mean tumor size ± SEM = 2,511.05 ± 83.64 mm 3 ), PA group (received probiotics but not anti-PD-1 antibody; mean tumor size ± SEM = 2,867.67 ± 144.60 mm 3 ), and NC group (did not receive probiotics nor anti-PD-1 antibody; mean tumor size ± SEM = 3,695.74 ± 134.39 mm 3 ) (Figure 1B). Notably, the anti-PD-1 treatment significantly reduced the tumor volume compared with other groups (P < 0.05 at day 24), suggesting that the anti-PD-1 treatment was effective in tumor suppression with or without probiotic supplementation. No significant difference was seen in the tumor volume between PA and NC groups at any monitored time point, suggesting that administration of Probio-M9 alone had no significant effect on tumor suppression.…”
Section: Probio-m9 Administration Improved the Efficacy Of Anti-pd-1-based Immunotherapymentioning
confidence: 87%
See 1 more Smart Citation
“…The score for the percentage area involvement (P) is as follows: 1 = 1–25%; 2 = 26–50%; 3 = 51–75%; and 4 = 76–100%. The total histological score was calculated as I + E + R + C + P [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…2019). Studies have shown that it can improve the immune response function of the body and reduce the degree of in ammation by Oral Probio-M9 (Xu et al 2021). Moreover it has a prevention and treatment effect on breast in ammation (Yang et al 2021), and has a good therapeutic effect on in ammatory bowel disease and breast cancer of rats (data not published).…”
Section: Introductionmentioning
confidence: 99%